Relationship of total iron content in beef to flavor attributes - Grobbel, J.P.; Dikeman, Michael E.; Milliken, George A.; Yancey, E.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The objective of our study was to evaluate the relationships among total iron content, myoglobin/total iron ratio, hemoglobin/total iron ratio, and flavor attributes in beef top sirloin, shoulder clod, and tenderloin muscles. Top sirloin (n=74), shoulder clod (n=68), and tenderloin (n=73) muscles from A or B maturity carcasses that were either USDA Slight or USDA Small marbling and of either normal pH (<5.7) or high pH (>6.0) were vacuum packaged, aged 35 days at 35ºF, and stored at -4ºF until analysis. A well trained, flavorprofile sensory panel determined flavor attributes on charbroiled steaks. Flavor attributes included beef flavor identification, bloody/serumy, brown roasted, livery, metallic, rancid, and sour. Concentrations of myoglobin and hemoglobin were determined by using high-pressure liquid chromatography. Total iron concentration was determined by using an atomic absorption spectrophotometer. The shoulder clod had greater total iron (P<0.05) than the top sirloin or tenderloin. Livery flavor increased (P<0.05) and beef flavor identification and brown roasted flavor decreased (P<0.05) in the top sirloin as total iron increased. Compared with the top sirloin and shoulder clod, the tenderloin had lower (P<0.05) myoglobin/total iron ratios and greater (P<0.05) hemoglobin/total iron ratios. At medium and high myoglobin/total iron ratios, samples with Slight marbling had more (P<0.05) livery flavor. At low myoglobin/total iron ratios, A-maturity samples had more (P<0.05) rancid off-flavor than B maturity samples. There were no relationships between hemoglobin/total iron ratios and flavor attributes. Total iron may contribute to livery flavor in the top sirloin, but total iron is not a reliable indicator of livery flavor.
Keywords: Beef; Iron content; Flavor; Myoglobin and hemoglobin concentrations